Effect Of Financial Inclusion On Women Empowerment: With Special Reference To Marginalized Working Women - R.L. Mangayarkarasi; Dr. R. Vasumathi (Revista Electronica de Veterinaria, 2024)
Literatures had proved that economic development helps in the promotion of gender equity. Further, the easy access for resources provided to women paves the way to several developmental outcomes. The strategy of inclusive growth requires that economic development is essential providing equal chances to all in the society, in particular the women in the marginalized sector. It had been recognized by the World Bank that economic growth is boosted up through the gender equality. Keeping all these points in view, the present study is an effort to examine the impact of financial inclusion over the empowerment of women. The sample population comprised of the marginalized working women in Pondicherry who has been selected as respondents through simple random sampling. The sample size is 100 and data has been gathered with the help of a questionnaire. The analytical tool adopted for data analysis is Multiple Regression and the results reveal that there is positive relationship between financial inclusion and marginalized women empowerment.